Migration, Temporality, and Capitalism Entangled Mobilities across Global Spaces (Springer International Publishing, 2018)
Bringing together a range of illustrative case studies coupled with fresh theoretical insights, this volume is one of the first to address the complexities and contradictions in the relationship between migration, time, and capitalism. While temporal reckoning has long fascinated anthropologists, few studies have sought to confront how capitalism fetishizes time in the production of global inequalities-historically and in the contemporary world. As it explores how the agendas of capitalism condition migration in Europe, North America, and Oceania, this collection also examines temporality as a feature of migrants' experiences to ultimately provide a theoretically robust and ethnographically informed investigation of migration and temporality within a framework defined by the political economy of capitalism. .